Tedarik zincirinde toplam kalite yönetimi - Kaplan, Selda (My University, 2003)
Ülkeler arası sınırların kalktığı ve dünyanın tek bir pazar olarak görüldüğü günümüzde, müşteri memnuniyetini hedefleyen Toplam Kalite Yönetimi, işletmelere içinde bulundukları pazarda rekabet üstünlüğü sağlamaktadır. Bir ürünün kalitesi, müşteriye ulaşıncaya kadar içinden geçtiği tüm süreçlerden etkilenmektedir. Böylece kalite kavramı tüm tedarik zinciri boyunca ele alınmalıdır. Gerçek rekabetin işletmeler ile işletmeler arası değil de tedarik zincirleri ile tedarik zincirleri arası olduğu şu günlerde kalitenin sürekliliğini sağlamak esastır. Bu çalışma ile işletmelerin Toplam Kalite Yönetimi ve etkili bir Tedarik Zinciri Yönetimine bakış açıları tespit edilmeye çalışılmış ve Toplam Kalite Yönetiminin, Tedarik Zincirine uygulanması durumunda, işletmelere getirileri değerlendirilmiştir. Name and Surname: Selda Kaplan Field: Management Programme : International Quality Management Supervisor: Assist. Prof. Dr. A. Ercan Gegez Degree Awarded and Date: Master – July 2003 Supply Chain Management, Total Quality Management

The importance of Total Quality Management has been realized more&more nowadays as the borders have been unestimated with the effect of globalization and the whole word seems to be a one huge market. Total Quality Management which mainly aims customer’s satisfaction provides competitive advantage to companies over market. The quality of one specific product is affected through whole processes until it reaches to customers. Thus, the quality concept should be considered as a continuous process within the supply chain. This days in which the real competition is not company against company but rather supply chain against supply chain, provided that continues quality is foundation. With this project, the management of Total Quality in firms and the different views of firms about Supply Chain Management, tried to be clarified. Also the advantages for the companies have been evaluated in this study if firms apply Total Quality Management to supply chain.
Keywords: Toplam Kalite Yönetimi